Opportunistic mobile air pollution monitoring: A case study with city wardens in Antwerp. (September 2016) - Van den Bossche, Joris; Theunis, Jan; Elen, Bart; Peters, Jan; Botteldooren, Dick; De Baets, Bernard
Abstract: The goal of this paper is to explore the potential of opportunistic mobile monitoring to map the exposure to air pollution in the urban environment at a high spatial resolution. Opportunistic mobile monitoring makes use of existing mobile infrastructure or people's common daily routines to move measurement devices around. Opportunistic mobile monitoring can also play a crucial role in participatory monitoring campaigns as a typical way to gather data. A case study to measure black carbon was set up in Antwerp, Belgium, with the collaboration of city employees (city wardens). The Antwerp city wardens are outdoors for a large part of the day on surveillance tours by bicycle or on foot, and gathered a total of 393 h of measurements. The data collection is unstructured both in space and time, leading to sampling bias. A temporal adjustment can only partly counteract this bias. Although a high spatial coverage was obtained, there is still a rather large uncertainty on the average concentration levels at a spatial resolution of 50 m due to a limited number of measurements and sampling bias. Despite of this uncertainty, large spatial patterns within the city are clearly captured. This study illustrates the potential of campaigns with unstructured opportunistic mobile monitoring, including participatory monitoring campaigns. The results demonstrate that such an approach can indeed be used to identify broad spatial trends over a wider area, enabling applications including hotspot identification, personal exposure studies, regression mapping, etc. But, they also emphasize the need for repeated measurements and careful processing and interpretation of the data. Graphical abstract: Highlights: An opportunistic mobile monitoring campaign is conducted with the collaboration of city employees. The opportunistic approach can identify broad spatial trends of the urban air quality. It is a challenge to collect sufficient data to cover both spatial and temporal variability. The evaluation of this set-up is relevant for participatory and crowdsourcing campaigns.